Baseline cluster of differentiation 22 fluorescent intensity correlates with patient outcome after Inotuzumab Ozogamicin treatment. Issue 4 (5th June 2022) - Sartor, Chiara; Arpinati, Mario; Chirumbolo, Gabriella; Dozza, Luca; Cristiano, Gianluca; Nanni, Jacopo; Marconi, Giovanni; Robustelli, Valentina; Vigliotta, Ilaria; Parisi, Sarah; Terragna, Carolina; Testoni, Nicoletta; et al.
Abstract: Antigen‐directed target therapy for B‐cell acute lymphoblastic leukemia (B‐ALL) is now the standard of care for relapsed/refractory (R/R) disease. A comprehensive determination of the target itself is mandatory to aid physician's choice. We determined baseline Cluster of differentiation 22 (CD22) expression percentage and fluorescent intensity on lymphoblasts of 30 patients with R/R B‐ALL treated with anti‐CD22 immunoconjugate drug Inotuzumab Ozogamicin (INO) and analyzed the impact of both parameters on patient outcome. Most patients (24/30, 80%) had a high leukemic blast CD22‐positivity defined as ≥90%. We did not observe a benefit in terms of complete remission, overall survival (OS) and duration of response (DoR) for patients with CD22 ≥ 90% versus CD22 < 90%. Concerning CD22‐FI quartile analysis we appreciated a trend for superior response rates in higher quartiles (Q2 ‐Q4 ) compared to Q1 and a significant benefit in terms of OS and DoR for patients with higher CD22‐FI. INO demonstrates to be effective also in patients with lower CD22 expression, but therapeutical benefits are more evident in patients with higher CD22‐FI. The evaluation of both CD22 percentage and CD22‐FI of the leukemic blast may help physicians in therapeutic choices for R/R B‐ALL patients when multiple treatment options are available, although no CD22 expression threshold can currently be identified below which INO should be considered not effective.